IMPLEMENTASI SISTEM PENJADWALAN MATA KULIAH BERBASIS WEB - Lutfiyah Dwi Setia (Department of Science and Technology Ibrahimy University, 2017)
The process of scheduling the course is a routine activity beginning of the academic year at vocational college. General consideration in the preparation of the schedule is the request of the lecturer concerned can not teach at any given time. The absence of lecture schedules and examinations simultaneously between lecturers, class, space or lecture time. Therefore the scheduling application in arranging the course schedule is built to accommodate various aspects of the above considerations. This application is built based on the web using PHP programming language with MySql database by following the rules of design and implementation of information systems and rules of preparation of the schedule of courses at Vocational High School .. Development of this scheduling application of the future course is needed to be implemented on each course, so scheduling process can be set more valid.